2022
DOI: 10.1177/15330338221141254
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Preoperative Albumin-to-Alkaline Phosphatase Ratio on Survival Outcome for Patients With Locally Advanced Oral Squamous Cell Carcinoma

Abstract: Background: This retrospective cohort study was to assess the prognostic value of preoperative albumin-to-alkaline phosphatase ratio (AAPR) on survival outcome for patients with locally advanced oral squamous cell carcinoma (LAOSCC). Methods: A total of 250 patients with LAOSCC receiving upfront radical surgery at a single institute from January 2008 to December 2017 were enrolled. The primary endpoint was the survival predictability of preoperative AAPR on the 5-year overall survival (OS), cancer-specific sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Alkaline phosphatase seems to be a regulator of immune response, involved in tumor growth regulation, metastasis, and progression. Recent evidence suggested that ALP can serve as a tumor-associated antigen and biomarker of cancer cell proliferation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline phosphatase seems to be a regulator of immune response, involved in tumor growth regulation, metastasis, and progression. Recent evidence suggested that ALP can serve as a tumor-associated antigen and biomarker of cancer cell proliferation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to AAPR<0.51, the pre-operative values of AAPR ≧0.51 were associated with a significantly higher OS (76.1% vs 48.5%), CSS (84.3% vs 66.4%), and DFS (68.9% vs 42.6%). A nomogram that includes both clinical-pathological characteristics and preoperative AAPR could accurately predict 5-year outcomes of locally advanced oral squamous cell carcinoma cases (46,47). The prognostic value of the AAPR was assessed for a cohort of 342 cases of HNC treated with concurrent chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…13 Serum albumin concentration is commonly employed as a means of assessing malnutrition, which have been found to be prognostically significant in patients with head and neck cancer. [14][15][16][17][18] Our previous studies had also reported that increasing postoperative complication with poor prognosis were associated with lower serum albumin concentration in patients with head and neck cancer. 19 To integrate the above biomarkers, Bernard et al introduced a new metric, the neutrophil-to-albumin ratio (NAR), which is calculated by dividing the absolute neutrophil count (ANC) by the serum albumin concentration.…”
mentioning
confidence: 85%
“…Meanwhile, malnutrition has also been frequently discussed in evaluating the condition and prognosis of cancer patients 13 . Serum albumin concentration is commonly employed as a means of assessing malnutrition, which have been found to be prognostically significant in patients with head and neck cancer 14–18 . Our previous studies had also reported that increasing postoperative complication with poor prognosis were associated with lower serum albumin concentration in patients with head and neck cancer 19 …”
Section: Introductionmentioning
confidence: 99%